Newly Modified Posterior Axilla Maneuver: Tilt and Kristeller Procedure - Sárközi, László; Hegedűs, András; Péterfi, István (Clinical Journal of Obstetrics and Gynecology, 2024)
Shoulder dystocia is a rare but severe complication of vaginal delivery with possibly serious consequences. Certain risk factors are associated with shoulder dystocia, but a general forecasting model is lacking. We present a Case report using a newly modified Posterior Axilla Maneuver technique that saved a 5.140 g (11 lbs. 5 oz.) newborn from shoulder dystocia. The child was born with Apgar 7/9, pH 7.17. Currently, there are no signs of any long-term sequelae. Our procedure comprised the following steps: 1. First, we pulled the posterior shoulder downwards - in the direction and to the outer surface of the perineum. 2. Then we pulled the posterior shoulder backward - toward the maternal spine - when it was already outside the perineum and finished extracting the posterior shoulder. 3. By completing the first two steps, a Tilt of the shoulder girdle was reached in the midsagittal plane, resulting in a backward slope for the shoulder girdle so that the anterior shoulder touched the symphysis slightly from the back in a skewed manner, freeing it from the initial impacted position. 4. We applied the Kristeller procedure only after dislodging the anterior shoulder from its initial impacted position. 5. We also applied the McRoberts Maneuver at the end of the process to increase the diameter of the birth canal.